Long-term Simultaneous Monitoring Observations of SiO and H2O Masers toward the Mira Variable WX Serpentis - Jang-Ho Lim; Jaeheon Kim; Se-Hyung Cho; Hyosun Kim; Dong-Hwan Yoon; Seong-Min Son; Kyung-Won Suh (The Astrophysical Journal Supplement Series)
We present the results from long-term simultaneous monitoring observations of SiO and H _2 O masers toward the Mira variable star WX Serpentis. This study has been conducted with 21 m single-dish radio telescopes of the Korean VLBI Network from 2009 June to 2021 June. Five maser lines were considered: SiO v = 1, 2, J = 1−0; SiO v = 1, J = 2−1, 3−2; and H _2 O 6 _1,6 –5 _2,3 transitions, with the SiO maser lines distributed near the stellar velocity and the H _2 O maser exhibiting an asymmetric line profile with five to six peaked components. Intense H _2 O maser emissions suddenly appeared in 2019 September, indicating flaring. The intensity variations of SiO and H _2 O masers are strongly correlated with the optical light curve (OLC) of the central star, with individual phase lags; the phase lag of the H _2 O maser relative to the OLC is larger than that of the SiO masers. The consequent phase difference between the SiO masers and the H _2 O maser likely indicates that their formation regions and main driving mechanisms are different from each other. The SiO masers in WX Ser exhibit a dominant single-peak velocity distribution, similar to other Mira variable stars. However, the H _2 O maser displays distinct morphological features, showing a radial acceleration and preferential intensity dominance at blueshifted velocities. This suggests that the H _2 O maser clouds of WX Ser are moving outward, thereby developing an asymmetric outflow owing to nonuniform material ejection from the stellar atmosphere. The findings confirm that an initial asymmetric outflow structure emerged during the thermally pulsing asymptotic giant branch phase, specifically in the Mira variable star stage.